Implementation of Portable Off-Grid Solar Water Pump for Irrigation Systems - Albert Sagala; Pandapotan Siagian; Indra Tambunan; Tennov Simanjuntak (Institute of Computer Science (IOCS), 2022)
The need for irrigation is absolute for the agricultural system. Water pump is a highly needed tool by society in providing clean water and irrigation. If we only rely on rainwater, the land becomes unproductive in the dry season. The unavailability of electricity in many locations in Indonesia is an obstacle for farmers to install drilled wells or draw water from rivers. In this research, a solar water pump system is designed that allows it to be moved easily. The solar pump uses a 100 Ah battery, a 120 WP solar panel and a 1000 watt inverter. The model has been tested to irrigate strawberry gardens in Pintubosi Village, Toba Regency. The pump has been running for 4 hours (12.00 – 16.00 AM) while irrigating and charging the battery are running simultaneously.